221k views
5 votes
Please help me on this one

Please help me on this one-example-1
User Pasi
by
5.5k points

2 Answers

2 votes

Answer:

b

Explanation:

User Meeka
by
5.8k points
7 votes

Answer:

Option b. 4*(a^4)/(b)

Explanation:

We have sqrt(16(a^8)(b^-2)).

We know that sqrt(a*b)=sqrt(a)*sqrt(b).

Applying this rule we have:

sqrt(16(a^8)(b^-2)) = sqrt(16)*sqrt((a^8)(b^-2)) = 4sqrt((a^8)(b^-2))

Also we know that:

sqrt(a/b) = sqrt(a)/sqrt(b)

Applying this rule we have:

4sqrt((a^8)(b^-2)) = 4sqrt(a^8)/sqrt(b^-2)

Also we know that

sqrt(a^b) = a^(b/2)

Applying this rule we have:

4*(a^8/2)*(b^-2/2) = 4*(a^4)(b^-1)

Last but no least, we know that:

a^-b = 1/(a^b)

Applying this rule we have:

4*(a^4)(b^-1) = 4*(a^4)/(b)